Unnatural amino acids as tool to study protein interaction - Müller, Nora (Jihočeská univerzita, 2023)
In this study, we investigate several gating loci present in the transmembrane region TM3 (L174, A177, V181, L185, F187, L188, V192) and TM4 (A254) of Orai1. These gating loci are known to alter the Orai1 channel activity upon conventional mutagenesis. The aim of the thesis was to incorporate proximity-dependent photocrosslinking unnatural amino acids (UAAs) p-azido-L-phenylalanine (Azi) and p-benzoyl-L-phenylalanine (Bpa) at these positions, enabling the observation of interaction sites between TM3 and TM4. However, our investigations remain inconclusive due to experimental challenges that were obtained during the timeframe of this Master Thesis.
Unnatural amino acids as tool to study protein interaction
Keywords: CRAC Channel Orai1; conformational studies; integration of UAAs; Photocrosslinking; CRAC Channel Orai1; conformational studies; integration of UAAs; Photocrosslinking